Photocatalytic Degradation of Methylene Blue (MB) by Cerium Doped Titanium Dioxide (Ce/TiO2) Under Uv-Visible Light Irradiation - Adi Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
Photocatalytic degradation of MB was applied using Ce-doped TiO2 under UV-visible light irradiation. The aim of this investigation is to improve the light absorption ability of Ce-doped TiO2 under UV-visible light irradiation to degradation of MB. The TiO2 catalyst was provided by the sol-gel method and addition doping of Ce with 1wt%, 2wt%, 3wt%, 4wt%, and 5wt% concentration. The characterization of photocatalyst has been observed through XRD, UV-vis spectroscopy, PL, and nitrogen absorption. Measurement of UV-Visible absorption showed that increased in dopant concentration in the range 1wt%–5wt% decreased the optical band gap of Ce-doped TiO2. Photocatalyst with doping 3wt% concentration of Ce showed the best photocatalytic activity. The effect of addition Ce successfully to prevent the growth of anatase phase TiO2, enhanced of surface area and enhanced the optical properties of TiO2. The result was effective to prevent the electron-hole recombination and increase the ability of photocatalytic activity in degrade of MB.